Challenges and Strategies in English Preparatory Program (EPP) Language Planning: An EPP Director’s Perspective - Ferrera, Renz; Macaraeg, Jonathan; Gutierrez, Joselito; Paulino, Freda (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study aims to explore the challenges experienced by an EPP director and the strategies that she applied in language planning during the EPP director’s first year of appointment in an international higher education institution in The Kingdom of Cambodia. In this qualitative research, case study was employed. Data were gathered via semi-structured interview conducted using Google Meet. The findings reveal that the EPP director encountered the three C’s of language planning challenges; namely, 1) cultural conflicts, 2) classroom challenges, 3) and coordination concerns. Amidst the challenges experienced by the EPP director during her first year of appointment, the she utilized the following strategies known as the three C’s of language strategies: 1) curriculum customization, 2) classroom engagement, and 3) communication. Despite ongoing challenges, the director's strategic adjustments have driven program growth such as the improvement of learning materials, student engagement, and decision-making procedures by meeting evolving student needs through curriculum customization, engagement enhancement, and collaboration. The program's flexibility and stakeholder focus have built resilience, enabling it to thrive despite limitations.